2015
DOI: 10.2522/ptj.20140282
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between Distance Ambulated as Part of Usual Care and Functional Exercise Capacity in Survivors of Critical Illness Upon Intensive Care Discharge: Observational Study

Abstract: Most participants ambulated at a low percentage of their measured exercise capacity. The 6MWT appears to be a safe and useful test for inpatients recently discharged from the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Specifically, earlier work in hospitalized adults has shown that the distance walked on the ward was, on average, less than 30% of what they achieved during an objective assessment of exercise capacity. 38 In this review, more than 70% of studies that prescribed either walking training or resistance training were based on the initial prescription on objective measures of physical function collected in each individual. Walking-based aerobic training programmes were most often prescribed based on the results of 6-minute walk test and resistance training programmes were most often prescribed based on the measure of a one-repetition maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, earlier work in hospitalized adults has shown that the distance walked on the ward was, on average, less than 30% of what they achieved during an objective assessment of exercise capacity. 38 In this review, more than 70% of studies that prescribed either walking training or resistance training were based on the initial prescription on objective measures of physical function collected in each individual. Walking-based aerobic training programmes were most often prescribed based on the results of 6-minute walk test and resistance training programmes were most often prescribed based on the measure of a one-repetition maximum.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol used for the 6MWT has been published previously. 26 If participants were using walking aids and supplemental oxygen on the ward, these were used during the 6MWT. Any assistance that the participant required to mobilize (e.g.…”
Section: -Minute Walk Testmentioning
confidence: 99%
“…That cannot be due to not having enough time to provide these patients with sufficient walking for exercise, because they only needed 6 minutes to achieve the distance covered during the test. 7 When training our patients we must apply essential exercise principles such as overload. Exercise and activity are not therapeutic when the intensity and duration are insufficient, even when the exercise is provided by a PT or PTA.…”
mentioning
confidence: 99%
“…Too often we provide interventions that are insufficiently rigorous. An example was published by Waters et al, 7 where hospital inpatients were tested with the 6-minute walk test 1 week after discharge from an intensive care unit. Not surprising were the findings that administration of the test was feasible and that subjects had impaired performance.…”
mentioning
confidence: 99%